PENGEMBANGAN SOAL UNTUK MENGUKUR KEMAMPUAN BERPIKIR TINGKAT TINGGI POKOK BAHASAN BARISAN DAN DERET BILANGAN DI KELAS IX AKSELERASI SMP XAVERIUS MARIA PALEMBANG - Lewy Lewy; Zulkardi Zulkardi; Nyimas Aisyah (Jurnal Pendidikan Matematika, 2009)
Teaching fast learning students is not enough by giving them ordinary mathematics problems. Teaching activities for fast learning students bring consequence for teacher to modify teaching activities from regular to activity that needs Higher Order Thinking skills. Therefore it is need to develop problems to measure higher order thinking skills.  This study aims to (1) produce a valid and practical prototype problems to measure Higher Order Thinking skills in Number Sequences and Series for Acceleration Class Grade IX (2) see the effects of the problems to measure higher order thinking skills on students’ achievement in Number Sequence and  Series was tried out to students of acceleration class grade IX .  This study use development research that consists of analyzing, designing, evaluating, and revising. The instrument for collecting data is written test. Test is used to see students’ achievement in Number Sequences and Series.  All data are analyzed using descriptive technique. Subjects in this research are students of Acceleration Class Grade IX of SMP Xaverius Maria Palembang. The total subject are 22 students The results of analysis are: (1) problems prototype which is developed has been valid and practical. (2) based on developing process  can be obtained  that problems which is developed contains potential effect to higher order thinking skills of Acceleration Class Grade IX of SMP Xaverius Maria Palembang shown by written test result score 35.59. It means that students’ thinking skill is good category. The final conclusion is the problems which is developed can be used to measure higher order thinking skills in Number Sequence and Series   Keywords:  problems to measure higher order thinking skills, number sequences and series, acceleration.